2023
DOI: 10.1007/s40520-023-02500-0
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a risk prediction model for intraoperative hypothermia in elderly patients undergoing total hip arthroplasty

Bin zhao,
Zhe zhu,
Wenwen Qi
et al.

Abstract: Aims To construct and validate an intraoperative hypothermia risk prediction model for elderly patients undergoing total hip arthroplasty (THA). Methods We collected data from 718 patients undergoing THA in a tertiary hospital from January 2021 to December 2022. Of these patients, 512 were assigned to the modeling group from January 2021 to April 2022, and 206 participants were assigned to the validation group from May 2022 to December 2022. A logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…This indicates that the incidence of hypothermia during pancreaticoduodenectomy was high, and that it was concentrated in the above four time periods. The overall incidence in this study was higher than that reported in studies by Desgranges [ 6 ], Dai [ 7 ], Zhao [ 8 ] and others. This may be because the participants in the present study were patients undergoing pancreaticoduodenal surgery and the complicated surgical procedures included the excision and reconstruction of intra-abdominal organs, resulting in a long duration of surgery (average 5.6 h).…”
Section: Discussioncontrasting
confidence: 77%
“…This indicates that the incidence of hypothermia during pancreaticoduodenectomy was high, and that it was concentrated in the above four time periods. The overall incidence in this study was higher than that reported in studies by Desgranges [ 6 ], Dai [ 7 ], Zhao [ 8 ] and others. This may be because the participants in the present study were patients undergoing pancreaticoduodenal surgery and the complicated surgical procedures included the excision and reconstruction of intra-abdominal organs, resulting in a long duration of surgery (average 5.6 h).…”
Section: Discussioncontrasting
confidence: 77%